Innovation in UI/UX design as a key to successful promotion of web resources - Samulinas, Stanislav; Zhytienova, Natalia (Professional Art Education, 2025)
Object. The purpose of the article is to analyze the impact of innovative trends in UI/UX design on the promotion of web resources, identify their relationship with user behavior metrics and SEO effectiveness, and outline the primary challenges and prospects for further development in this area. Methods and methodology. The study employs a comprehensive analysis of current UI/UX design trends, including micro-animations, dark mode, VR/AR technologies, adaptive and personalized content, and their effects on user experience and SEO factors. Special attention is given to methods integrating UI/UX principles with modern SEO strategies, specifically the SXO (Search Experience Optimization) approach. Scientific novelty. It consists in the systematization and comprehensive analysis of the relationship between innovative trends in UI/UX design and the effectiveness of web resource promotion from the standpoint of UX metrics and SEO. For the first time, attention is focused on the need for an integrated approach to implementing innovations, in particular by applying the SXO concept, which allows you to simultaneously satisfy the requirements of users and search engine algorithms. The results. The primary results include identifying key innovative UI/UX trends such as micro-interactions, adaptive content, immersive experiences (VR/AR), dark mode, and personalization. These trends significantly influence user experience by reducing bounce rates, increasing user engagement, and improving conversion rates. It has been proven that search engines increasingly factor user experience indicators into rankings, demonstrating the growing convergence of UX and SEO, culminating in the SXO (Search eXperience Optimization) concept. Essential implementation methods were systematized, highlighting user-centered design, A/B testing, prototyping, and the application of design systems. Conclusions. Innovations in UI/UX design are pivotal for the successful promotion of web resources in today’s digital landscape. Effective implementation of UI/UX trends contributes not only to enhanced user experiences but also positively affects business outcomes, such as improved conversions, user retention, and SEO visibility. Future research directions include exploring deeper integrations of UX and SEO strategies, maximizing personalization and context-awareness, and developing standards and educational programs for evaluating and implementing effective UI/UX solutions.